Informed consent for interventions in stable coronary artery disease: problems, etiologies, and solutions. - Chandrasekharan, D; Taggart, D (2011)
The objective of this review was to determine whether patients undergoing percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) (1) understand the aims of the proposed intervention, and (2) whether they are offered alternative and potentially more effective therapies, as required for the process of informed consent. We performed a systematic review of Medline for observational studies of patient understanding and perceptions of coronary revascularization and of the consent process. Data extraction was of patient perceptions of expected symptomatic and prognostic benefits of PCI and CABG, and the proportion of patients offered potential alternative treatments. Eight studies were identified, of which seven were relevant to PCI and three to CABG. On average, 55% of patients correctly believed that PCI would improve symptoms, while 78% erroneously believed that PCI would extend life expectancy and 71% erroneously believed PCI would prevent future myocardial infarction. On average, over 80% of patients correctly identified that CABG would improve symptoms, reduce the risk of myocardial infarction and extend life expectancy. In the three studies that examined whether alternative therapies were discussed, 68% of PCI patients and 59% of CABG patients reported no such discussion. In conclusion, a large proportion of patients undergoing coronary interventions do not appear to understand the rationale for treatment and have erroneous perceptions regarding expected benefits. Moreover, patients are frequently not offered potentially more effective alternative therapies. This raises important questions about the adequacy of the current informed consent process. We recommend a multidisciplinary team approach as the most obvious way to remedy current practice.